Potassium application for sugarcane in a sandy loam Oxisol of the Brazilian Cerrado - Rodrigues, Alvaro do Nascimento; Carneiro, Leandro Flávio; Carneiro, Daniella Nogueira Moraes; Timossi, Paulo César; Rein, Thomaz Adolpho; Santos Junior, João de Deus Gomes dos (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate rates and methods of potassium application for plant cane (Saccharum spp.) grown in a dystrophic Typic Haplustox with a sandy loam texture in the Brazilian Cerrado. The experiment was carried out in the municipality of Aporé, in the state of Goiás, using the RB92579 sugarcane variety. The experimental design was randomized complete blocks, with three replicates, in a 5x3 factorial arrangement, with five potassium rates (0, 60, 110, 160, and 200 kg ha-1 K2O as potassium chloride) and three application methods (100% at the bottom of the planting furrow and covered with soil, 100% side-dressed on the sugarcane rows 60 days after planting, and 50% in the planting furrow and 50% side-dressed). The amount of potassium in the stalks in the control treatment was greater than that of the potassium stock extractable by Mehlich-1 in the 0–60 cm soil layer. Stalk and sugar yields increase linearly with potassium rates, approximately 20% with 200 kg ha-1 K2O compared with the control treatment (without potassium). Potassium content in stalks also increases with potassium rates. There is no significant effect of the potassium application methods on stalk and sugar yields and on cane quality variables.